Peran Guru Pendidikan Agama Islam Dalam Mengembangkan Karakter Mulia Siswa - Alfi Dzikri, Fawaz Akbar; Hafidz, Hafidz (Kamaya: Jurnal Ilmu Agama, 2025)
Teachers of Islamic Religious Education (PAI) are essential to students' practical contributions because they help them develop moral character by imparting Islamic values. This entails setting a good example, encouraging moral consciousness, and inspiring students to absorb and carry out these principles on a regular basis. In addition to helping students build strong relationships with Allah SWT and others, Islamic Religious Education (PAI) teachers who have a thorough understanding of character education can also help students develop into people who are honest, fair, responsible, empathetic, and honest. Descriptive qualitative methodology was employed, and a literature study was used to gather data. According to the study's analysis, pupils' development of noble character is greatly aided by their perception of Islamic Religious Education (PAI) teachers as role models. Islamic Religious Education (PAI) instructors might have a thorough understanding of Islamic religious concepts and moral principles, which are essential for cultivating noble character, thanks to insight into character education. Teachers of Islamic Religious Education (PAI) should keep refining their character education through professional communities, reading, and training.